Reduced impact logging guidelines for lowland and hill dipterocarp forest in Indonesia - Sist, P.; Dykstra, D.P.; Fimbel, R. (Center for International Forestry Research, 1998)
This report describes Reduced-Impact Logging(RIL) which will be implemented in the lowland and hill dipterocarp forest of the Bulungan Model Forest project in East Kalimantan, Indonesia. It is anticipated that through the implementation and supervision of the RIL practices described in this document, the timber concession operators (INHUTANI II) can expect to: reduce disturbances to soil and residual vegetation by at least 50% in comparison with conventional logging operations where these guidelines are not applied; limit overall direct impacts to the forest <25%; conserve wildlife and other forest resources, including non timber forest products (NTFPs), threatened and endangered species, keystone plant resources, and water; diminish direct logging costs by at least 15%; and protect the long-term integrity and value of the permanent forest estate